A dinâmica do investimento estrangeiro direto realizado pelos Brics (1995-2013) - Giuliano Contento de Oliveira; Paulo José Whitaker Wolf (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– Over the past decades, Brazil, Russia, India and China (BRICs) have assumed an important role in international relations, in particular with regard to the foreign direct investment (FDI). This group of economies, albeit under different intensities, ceased to be mere recipients of FDI to become important source of this kind investment. Thus, this study aims to explore the dynamics of the FDI of the BRICs, in order to capture its main conditioning factors, their trajectory, their structure and their major destinations throughout the period 1995-2013. It was verified the Chinese FDI leadership in this process, although the other countries that compose the group have increased in a significant way their respective FDI stocks between the beginning and the end of the considered period. In addition, significant differences were verified with regard to the main determining factors of these investments of BRICs, as well as to its structure and to its most important destinations. Moreover, after the outbreak of the global crisis in 2008 these differences have become even more evident. This study allows concluding, therefore, that the success of this process requires initiatives to ensure that companies in those countries are able to compete on the same conditions as those of the developed countries in strategic sectors.
Keywords: F00; F21; F23; F63; 330; foreign direct investment (FDI); BRICs; corporations' internationalization